2014
DOI: 10.1039/c4nr01296h
|View full text |Cite
|
Sign up to set email alerts
|

A metal–organic framework as a chemical guide to control hydrogen desorption pathways of ammonia borane

Abstract: We report that ammonia borane with a high uptake capacity for hydrogen can be encapsulated in a metal-organic framework (MOF) via capillary action, where the MOF functions as a chemical guide to control the hydrogen desorption pathways of ammonia borane by releasing only pure hydrogen, lowering its hydrogen desorption temperature, and suppressing its volumetric expansion during hydrogen desorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…It was reported that AB impregnated in MOF-5 demonstrated reduced T d and E a due to the nanoconfinement phenomenon. 29,30 On the other hand, several publications claim to have AB confined in MOFs by physical milling method. For instance, Wang et al attributed improved dehydrogenation properties of AB@MOF to nanoconfinement effect.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that AB impregnated in MOF-5 demonstrated reduced T d and E a due to the nanoconfinement phenomenon. 29,30 On the other hand, several publications claim to have AB confined in MOFs by physical milling method. For instance, Wang et al attributed improved dehydrogenation properties of AB@MOF to nanoconfinement effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Applying MOFs to AB nanoconfinement, for example, with chemical deliquesce method, in which AB crystals are dissolved in solution blending with suspended MOFs and further recrystallized after solvent removal, the AB@MOF composites desorb hydrogen at lowered temperature with improved kinetics compared to neat AB. It was reported that AB impregnated in MOF-5 demonstrated reduced T d and E a due to the nanoconfinement phenomenon. , On the other hand, several publications claim to have AB confined in MOFs by physical milling method. For instance, Wang et al attributed improved dehydrogenation properties of AB@MOF to nanoconfinement effect .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, despite these merits, there are technical barriers preventing AB to be practically used as an on-board energy source, such as its slow thermal kinetics below 100 C and unwanted by-products including ammonia (NH 3 ), diborane (B 2 H 6 ), and borazine (B 3 H 6 N 3 ), which will poison the catalyst in a proton membrane fuel cell. 2,3,[6][7][8] To date, a number of ways have been investigated to tackle the above mentioned issues including the use of metal catalysts 3,[9][10][11][12][13][14][15][16][17] or metal-free catalysts, [18][19][20] the formation of metal hydrides, [21][22][23] the realisation of metal or methane substitution, [24][25][26] the utilisation of ionic liquid, 27,28 additives, 29,30 or nanoconfinement 8,[31][32][33][34][35][36][37][38][39][40] etc. Significant improvements on lowering the hydrogen release temperatures, improving the kinetics and avoiding the emissions of those harmful by-products have been made.…”
Section: Introductionmentioning
confidence: 99%
“…14,23 Jeong, H. M. and colleagues reported an AB@MOF-5 thermal dehydrogenation system, but release of NH 3 was not described and the important effect of the unsaturated coordinated metal sites of MOFs in the AB-MOF system was not mentioned. 26 However, the formation of NH 3 is an important issue because even a small amount of NH 3 poisons the catalysts of proton exchange membrane fuel cells.…”
Section: Introductionmentioning
confidence: 99%